Comparative study of transabdominal preperitoneal versus open Lichtenstein hernia repair in primary inguinal hernia - Zargar, Owais-ul-umer; Ashraf, Nashrah; Albina, Ayat; Iqbal, Javed; Dhingra, N. C. (International Journal of Research in Medical Sciences, 2022)
Background: Inguinal hernia repair is one of the most commonly performed surgery in surgical practice and has evolved through various techniques. However, which technique is gold standard is still a topic of debate and the clinical studies are not adequate to show clear benefits of one technique over another. Objective was to compare the outcome of transabdominal preperitoneal repair (TAPP) versus open Lichtenstein tension free mesh repair in primary inguinal hernia. Methods: This retrospective cohort study was conducted in a tertiary care hospital with sample size of 80 patients (40 cases in each group) and these patients were compared in terms of operative time, complications, duration of hospital stay, postoperative recovery, postoperative pain and timing of return to normal activity and work. Results: On comparing the results of our study we found that in unilateral cases the operating time was greater in the TAPP group than the Lichtenstein group; however, in the bilateral cases, the operating time was significantly greater in the Lichtenstein repair group than the laparoscopic TAPP group. The incidence of post operative complications was lower in TAPP group (8.2%) then in open hernia repair group (21.6%). The time to return to normal activity was also lower for laparoscopic group in both unilateral and bilateral cases. Conclusions: It can be concluded that laparoscopic TAPP repair offers significant advantage over open tension free mesh hernioplasty in terms of lesser post operative pain, lesser complications and early return to normal activity, better cosmetic outcomes, and less persisting pain but it is associated with a higher operative time depending on surgeon’s expertise, more costly for the patient and there is no significant difference in early post operative complications.